The pentahlix strategy in sustainable tourism-based regional economic development in Gili Trawangan - Wahyunadi Wahyunadi; Nurul Silviana (Jurnal Pariwisata Pesona, 2026)
Sustainable tourism in Gili Trawangan faces a fundamental dilemma in balancing economic, social, and environmental dimensions, where efforts to maximize one dimension often result in sacrifices in other dimensions. This study aims to formulate a Pentahelix strategy model that can overcome the trade-offs between these three dimensions in the development of sustainable tourism in Gili Trawangan as a small island destination. The research method uses a descriptive-analytical qualitative approach with a case study design through in-depth interviews with informants representing the five elements of Pentahelix (government, community, business, academia, and media) selected through snowball sampling and analyzed using the Miles and Huberman model. The results of the study identified three main dilemmas in tourism development practices: first, the trade-off between aggregate economic growth and fair distribution of benefits, which resulted in economic leakage; second, the paradox of strong social resilience in community-business relations but a lack of trust in the government due to repeated program failures and unresponsive communication; third, the gap between awareness of the environmental crisis and the lack of concrete action, which has led to multidimensional degradation and the absence of calculation and implementation of carrying capacity, even though all parties recognize its urgency. Based on these findings, this study formulates a transformative-systemic strategy model for each element of the Pentahelix, including strengthening oversight and specific regulations for small islands by the government, optimizing community-based tourism and participatory conservation by communities, commitment to sustainable practices and holistic collaboration by businesses, evidence-based policy studies with quality tourism advocacy by academics, and solution journalism practices with public oversight functions by the media, which can synergistically balance economic growth, social welfare, and environmental conservation.